2018
DOI: 10.1007/5584_2018_144
|View full text |Cite
|
Sign up to set email alerts
|

Physical Training and Cardiac Rehabilitation in Heart Failure Patients

Abstract: Regardless of advances in medical and interventional treatment of cardiovascular disease (CVD), a limited number of patients attend a cardiac rehabilitation (CR) programme on a regular basis. Due to modern therapies more individuals will be surviving an acute cardiovascular event, but the expected burden of chronic heart failure will be increasing worldwide.However, both in high- and low-income countries, secondary prevention after an acute myocardial infarction or stroke has been implemented in less than a ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 110 publications
0
12
0
2
Order By: Relevance
“…To improve the reliability of the research, an expanded sample size is needed in the future. As the incidence of heart disease increases in middle-aged and elderly people, CVD has become the main cause of death (18) CHD, but also significantly improves the quality of life of patients (5). Through the meta-analysis of the original data of the 8 studies, we found that HIIT can improve the patient's cardiac function and prognosis.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To improve the reliability of the research, an expanded sample size is needed in the future. As the incidence of heart disease increases in middle-aged and elderly people, CVD has become the main cause of death (18) CHD, but also significantly improves the quality of life of patients (5). Through the meta-analysis of the original data of the 8 studies, we found that HIIT can improve the patient's cardiac function and prognosis.…”
Section: Discussionmentioning
confidence: 91%
“…Cardiac rehabilitation training accelerates blood circulation, improves myocardial support capacity, promotes cardiac rehabilitation, and reduces the risk of disability and death. Many studies have confirmed that cardiac rehabilitation is safe and effective (5). However, it has not been fully utilized in clinical work.…”
Section: Original Articlementioning
confidence: 99%
“…Of the 56.4 million estimated worldwide deaths in 2015, about 54% occurred in consequence of cardiovascular diseases (CVD) [ 46 ]. In this context, it has been clearly shown that physical activity and a healthy lifestyle significantly decrease the risk of CVDs and their worsening [ 47 ]. Accordingly, a large number of cardiac rehabilitation (CR) programs have been developed to treat CVDs in an attempt of preventing secondary events.…”
Section: Exercise and Sirtuins In Cardiovascular Diseasesmentioning
confidence: 99%
“…Of the 56.4 million deaths worldwide in 2015, 54% were due to cardiovascular diseases (CVD) [45]. In this context, it has been clearly shown that physical activity and a healthy lifestyle significantly decrease the risk of CVDs and their worsening [46]. Accordingly, a large number of cardiac rehabilitation (CR) programs has been developed to treat CVDs attempting to prevent secondary events.…”
Section: Exercise and Sirtuins In Cardiovascular Diseasesmentioning
confidence: 99%